Calanthe sieboldopsis (Orchidaceae, Epidendroideae, Collabieae), a new species from Luoxiao Mountains, eastern China - Bo-Yun Yang; Huo-Lin Luo; Wei-Chang Huang; Dong-Jin Xiong; Shao-Lin Tan; Bo Li (PhytoKeys, 2020)
Calanthe sieboldopsis, a new species, is here described and illustrated from Luoxiao Mountains, Jiangxi Province, eastern China. It is morphologically similar to C. sieboldii Decne. ex Regel, but differs from the latter in having smaller flowers, longer spurs, rectangular mid-lobes with emarginate apex (vs. elliptic mid-lobes with mucronate apex), disc with 3 ridges and the proximal ends of the lateral 2 ridges enlarged with light reddish spots and minute white hairs (vs. disc with 5 ridges and 2 rows of white short hairs at base) and pollinia equal in size (vs. unequal in size). A preliminary risk-of-extinction assessment, according to the IUCN Red List Categories and Criteria, is given for the new species.